The paradox of a forced election. (Journal of Parents and Teachers, 2014)
This article offers the story of Tatiana, a girl with great gifts for music that her parents encouraged when she was little, and not so much when she grew up. In the end, the author introduces a series of questions to promote reflection.
Keywords: Story; music; dream; illusion; obsession; struggle for what one wants.